2017
DOI: 10.3390/molecules22101762
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly with 2,6-Bis(1-(pyridin-4-ylmethyl)-1H-1,2,3-triazol-4-yl)pyridine: Silver(I) and Iron(II) Complexes

Abstract: A new “click” ligand, 2,6-bis(1-(pyridin-4-ylmethyl)-1H-1,2,3-triazol-4-yl)pyridine (L) featuring a tridentate 2,6-bis(1,2,3-triazol-4-yl)pyridine (tripy) pocket and two pyridyl (py) units was synthesized in modest yield (42%) using the copper(I) catalyzed azide-alkyne cycloaddition (CuAAC) reaction. The coordination chemistry of the ligand with silver(I) and iron(II) ions was examined using a battery of solution (1H and DOSY (diffusion ordered spectroscopy) nuclear magnetic resonance (NMR), infrared and absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…We investigated the self‐assembly properties of the metallo‐ligands and host‐guest systems with silver(I) ions. It was hoped that the use of labile, coordinatively pliant Ag I ions would allow the formation of larger assemblies or networks while still leaving the host‐guest interaction as the dominant factor in the self‐assembly process …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We investigated the self‐assembly properties of the metallo‐ligands and host‐guest systems with silver(I) ions. It was hoped that the use of labile, coordinatively pliant Ag I ions would allow the formation of larger assemblies or networks while still leaving the host‐guest interaction as the dominant factor in the self‐assembly process …”
Section: Introductionmentioning
confidence: 79%
“…It was hoped that the use of labile, coordinatively pliant Ag I ions would allow the formation of larger assemblies or networks whiles till leaving the host-guest interaction ast he dominantf actor in the self-assembly process. [29] Results and Discussion…”
Section: Introductionmentioning
confidence: 99%
“…1): the 3,5-btp motif has been extensively studied in the context of anion recognition, and deriva- tives containing an N-alkylated pyridinium group and/or halotriazole groups for halogen bonding have proven to be highly effective in this regard. [21][22][23] The 2,6-btp motif has primarily been used for coordination to a wide range of metal ions, [24][25][26][27][28][29][30][31][32][33] but has also been used for anion recognition [34][35][36] and anion binding catalysis 37 (the reader is directed to a recent review for a comprehensive overview of the chemistry of the 2,6-btp motif 20 ). Interestingly, Byrne and Gunnlaugsson have also demonstrated that the 2,6-btp motif can self-recognise through C-H⋯N hydrogen bonding, and have used this recognition to template the formation of catenanes.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Two isomers of the btp motif have been commonly studied (Figure 1): the 3,5-btp motif has been extensively studied in the context of anion recognition, and derivatives containing an N-alkylated pyridinium group and/or halotriazole groups for halogen bonding have proven to be highly effective in this regard. [21][22][23] The 2,6-btp motif has primarily been used for coordination to a wide range of metal ions, [24][25][26][27][28][29][30][31][32][33] but has also been used for anion recognition [34][35][36] and anion binding catalysis 37 (the reader is directed to a recent review for a comprehensive overview of the chemistry of the 2,6-btp motif 20 ). Interestingly, Byrne and Gunnlaugsson have also demonstrated that the 2,6-btp motif can selfrecognise through C-H•••N hydrogen bonding, and have used this recognition to template the formation of catenanes.…”
Section: Introductionmentioning
confidence: 99%